Slaptosios tarnybos vieta totalitarinėje SSRS - Burinskaitė, Kristina (Lietuvos istorijos studijos, 2008)
The Soviet secret service was one of the main pillars of the totalitarian Soviet system. The Bolshevik party formulated its policy according to communist ideology, where violence and dictatorship were among the most important elements. The Soviet secret service helped to implement their goals, consolidate Bolshevik power, and maintain the regime. But it did not implement just punitive and coercive functions; the Bolsheviks prescribed to them also political and ideological functions—to help the communist party implement its domestic and foreign policy, and to protect the communist system and ideology. Such functions made this institution exceptional in the USSR. Despite these important functions, the relationship between the communist party and the Soviet secret service was quite complicated and changeable. While the Cheka, GPU, and KGB were strictly subordinated to the party, Stalin made it his instrument in fighting his personal enemies and used it against the party itself in the 1930s. From 1954 to 1991, the communist party tried to strengthen political and party control over the KGB by introducing party institutions inside the KGB and departments of the administrative agency. The party organization organized and implemented educational and ideological work with personnel, which was important for personnel motivation, influencing its methods and usage of terminology. The department of the administrative agency had some influence over personnel appointments. However, these structures weren’t sufficient for controlling the KGB. After Stalin’s death in 1953, when the Soviets began to change the implementation of their domestic and foreign policy, the KGB also changed its activities and methods. The KGB began to more frequently use ideological means and prophylactics, which helped in quashing dissidents. The ideological nature of the KGB became more apparent in occupied countries because of the ideological treatment of people in those countries and the anti-Soviet movement. This influenced KGB activities and methods. The KGB and the communist party were the main pillars of the communist regime in Lithuania. The KGB helped the communists maintain their power and fight against anti-Soviet forces in Lithuania and emigration.